Smart material based on boron crosslinked polymers with potential applications in cancer radiation therapy - José Vedelago (Nature Portfolio, 2021)
Abstract Organoboron compounds have been playing an increasingly important role in analytical chemistry, material science, health applications, and particularly as functional polymers like boron carriers for cancer therapy. There are two main applications of boron isotopes in radiation cancer therapy, Boron Neutron Capture Therapy and Proton Boron Fusion Therapy. In this study, a novel and original material consisting of a three-dimensional polymer network crosslinked with $$^{10}$$ 10 B enriched boric acid molecules is proposed and synthesized. The effects of the exposition to thermal neutrons were studied analyzing changes in the mechanical properties of the proposed material. Dedicated Monte Carlo simulations, based on MCNP and FLUKA main codes, were performed to characterize interactions of the proposed material with neutrons, photons, and charged particles typically present in mixed fields in nuclear reactor irradiations. Experimental results and Monte Carlo simulations were in agreement, thus justifying further studies of this promising material.